The responsibility of marketing and legislation in childhood obesity - Szűcs, Róbert Sándor (Applied Studies in Agribusiness and Commerce, 2012)
The purchasing power of youth is considerable; they are the market of the future. , the young generation is the most influenced and vulnerable segment of the economy. The greatest problem of the influencing of our children is the rising cost of childhood obesity. The health care system cannot keep up with the pressure of obesity. Today, the risk of obesity is a bigger problem than smoking or alcoholism. The greatest problem is that youth underestimates the cost and risk of consumption of foods with high levels of fats, sugar and/or salt.